AKTIVITAS DAN SUMBER PENDAPATAN PETANI MISKIN BERLAHAN SEMPIT DI DAERAH SAWAH TADAH HUJAN DATARAN RENDAH (Kasus: Dua Desa di Kabupaten Bojonegoro ) - DARWIS, VALERIANA; NURMANAF, A. ROZANY (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 3 November2004, 2012)
There were several criteria that stick on a poor family, which are law educational level, the biggest proportion of their income from the farming activity and the small farm land ownership. Commonly the poor farm household in the study location owned a plot of rainfed and a plot of upland which avarage about 0.279 ha and 0.2 ha. The cropping patern on rainfed was rice and secondary crops was tobacco. By existing planted area their minimal living requirement mostly couldn’t be fulfilled and needed other sources. Income from farming activity in the last year was 42.77 percent and the other 57.23 percent came from non agricultural sector. Although allocated time was greater in farming activity, however the income was lower than from non agricultural https://www.budidayatani.com . To alleviate poverty mainly of those small scale farmer, an increasing water resourse was required in order to increase land productivity. Besides, quidance of farming technology practices and support were require sector.
Keywords: Poor farmer, Small Farm Land Ownership, Rainfed, Agricultural, Non Agricultural, Land Produktivity, Water Resourse, Poverty Alleviation.